Answer:
20. 2x+y
21. 4
22. x+y
Step-by-step explanation:
20. <u>9</u><u>x</u><u>+</u><u>2</u><u>y</u><u> </u>- <u>x-2</u><u>y</u><u> </u><u> </u> find your LCM
4 4
=<u>(</u><u>9</u><u>x</u><u>+</u><u>2</u><u>y</u><u>)</u><u>-</u><u>(</u><u>x-2y</u><u>)</u><u> </u> clear bracket
<u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u>4
=<u>9</u><u>x</u><u>+</u><u>2</u><u>y</u><u>-</u><u>x</u><u>+</u><u>2</u><u>y</u><u> </u> collect terms
4
=<u>9</u><u>x</u><u>-</u><u>x</u><u>+</u><u>2</u><u>y</u><u>+</u><u>2</u><u>y</u>
<u> </u> 4
=<u>8</u><u>x</u><u>+</u><u>4</u><u>y</u><u> </u> factorize
<u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u>4
=<u>4</u><u>(</u><u>2</u><u>x</u><u>+</u><u>y</u><u>)</u>
<u> </u><u> </u> 4
=2x+y
with this, you will understand the following
21. <u>4</u><u>x</u> + <u>8</u><u>y</u>
x+2y x+2y
=<u>4</u><u>x</u><u>+</u><u>8</u><u>y</u>
x+2y
=<u>4(x+2y)</u>
x+2y
=4
22. <u>2</u><u>x</u><u>-</u><u>y</u><u> </u>+ <u>2</u><u>x</u><u>+</u><u>5</u><u>y</u>
4 4
=<u>2</u><u>x</u><u>-</u><u>y</u><u>+</u><u>2</u><u>x</u><u>+</u><u>5</u><u>y</u>
4
=<u>4</u><u>x</u><u>+</u><u>4</u><u>y</u>
4
=<u>4(</u><u>x</u><u>+</u><u>y</u><u>)</u>
4
=x+y